2016
DOI: 10.1002/mnfr.201600121
|View full text |Cite
|
Sign up to set email alerts
|

Vinegar as a functional ingredient to improve postprandial glycemic control—human intervention findings and molecular mechanisms

Abstract: Type 2 diabetes prevalence worldwide is increasing and the burden is particularly high in Asian countries. Identification of functional food ingredients to curb the rise of diabetes among various Asian population groups is warranted. Vinegar is widely consumed throughout Asia, where the principle bioactive component is acetic acid. This review has collated data from human intervention trials to show that vinegar consumption seems more effective in modulating glycemic control in normal glucose-tolerant individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 104 publications
(164 reference statements)
3
23
0
Order By: Relevance
“…For example, in our acute studies ( 19 , 24 ) we included overweight and obese individuals with average fasting acetate concentrations of approximately 20–50 µmol/L, whereas in another study of our group with insulin resistant obese individuals markedly higher acetate concentrations of approximately 70–90 µmol/L have been found ( 26 ). In addition, a kinetic study showed that the acetate clearance rate is lower and the half-life is longer in type 2 diabetic patients when compared with healthy normoglycaemic controls ( 27 ). This suggests a disturbed uptake and/or metabolism of acetate, which might be relevant to elicit acetate-induced metabolic effects and cell signaling in peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our acute studies ( 19 , 24 ) we included overweight and obese individuals with average fasting acetate concentrations of approximately 20–50 µmol/L, whereas in another study of our group with insulin resistant obese individuals markedly higher acetate concentrations of approximately 70–90 µmol/L have been found ( 26 ). In addition, a kinetic study showed that the acetate clearance rate is lower and the half-life is longer in type 2 diabetic patients when compared with healthy normoglycaemic controls ( 27 ). This suggests a disturbed uptake and/or metabolism of acetate, which might be relevant to elicit acetate-induced metabolic effects and cell signaling in peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Acetate administration was also shown to reduce the size of intracellular lipid droplets in the same rat model of diabetes, and the authors propose that acetate levels act, in general, to counter the effects of reduced insulin and associated fat accumulation (Yamashita et al, 2009). In a review of studies on the effects of vinegar in diabetic and non-diabetic humans, it was concluded that vinegar lowers post-prandial glucose levels and increases insulin sensitivity in non-diabetics, but did not have the same positive effects in diabetic patients (Lim et al, 2016). This contrast highlights the context-specific beneficial effects of acetate on human health, where acetate metabolism or signaling can have distinct effects depending on whether an individual is healthy or has an underlying disease.…”
Section: Diabetesmentioning
confidence: 99%
“…This is also suggested by a recent narrative review. 41 Nevertheless, current evidence strongly supports the fact that vinegar does have favorable effect on carbohydrate metabolism that could be exploited in the management of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 90%